Does a new case-based payment system promote the construction of the ordered health delivery system? Evidence from a pilot city in China - Huanyu Shi; Zhichao Cheng; Zhichao Liu; Yang Zhang; Peng Zhang (BMC, 2024)
Abstract Background The construction of the ordered health delivery system in China aims to enhance equity and optimize the efficient use of medical resources by rationally allocating patients to different levels of medical institutions based on the severity of their condition. However, superior hospitals have been overcrowded, and primary healthcare facilities have been underutilized in recent years. China has developed a new case-based payment method called "Diagnostic Intervention Package" (DIP). The government is trying to use this economic lever to encourage medical institutions to actively assume treatment tasks consistent with their functional positioning and service capabilities. Methods This study takes Tai'an, a DIP pilot city, as a case study and uses an interrupted time series analysis to analyze the impact of DIP reform on the case severity and service scope of medical institutions at different levels. Results The results show that after the DIP reform, the proportion of patients receiving complicated procedures (tertiary hospitals: β3 = 0.197, P < 0.001; secondary hospitals: β3 = 0.132, P = 0.020) and the case mix index (tertiary hospitals: β3 = 0.022, P < 0.001; secondary hospitals: β3 = 0.008, P < 0.001) in tertiary and secondary hospitals increased, and the proportion of primary-DIP-groups cases decreased (tertiary hospitals: β3 = -0.290, P < 0.001; secondary hospitals: β3 = -1.200, P < 0.001), aligning with the anticipated policy objectives. However, the proportion of patients receiving complicated procedures (β3 = 0.186, P = 0.002) and the case mix index (β3 = 0.002, P < 0.001) in primary healthcare facilities increased after the reform, while the proportion of primary-DIP-groups cases (β3 = -0.515, P = 0.005) and primary-DIP-groups coverage (β3 = -2.011, P < 0.001) decreased, which will reduce the utilization efficiency of medical resources and increase inequity. Conclusion The DIP reform did not effectively promote the construction of the ordered health delivery system. Policymakers need to adjust economic incentives and implement restraint mechanisms to regulate the behavior of medical institutions.